2015
DOI: 10.1002/pd.4681
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblast retrieval and isolation from the cervix (TRIC) is unaffected by early gestational age or maternal obesity

Abstract: Objective The objective of this study is to evaluate whether trophoblast yield obtained by trophoblast retrieval and isolation from the cervix (TRIC) is affected by pregnancy outcome, gestational age (GA) at retrieval, maternal body mass index (BMI), parity, or maternal age. Methods TRIC was performed on 224 ongoing pregnancies between 5–20 weeks GA. Trophoblast cells were isolated from cervical cells using anti-human leukocyte antigen (HLA)-G antibody coupled to magnetic nanoparticles. Purity was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…However, those studies have reported variable results and it is difficult to conclude if there is a definite association between recovered fetal cell numbers and gestational age. [18][19][20][21] Furthermore, there are only two previously reported studies in which the influence of BMI on the number of fetal cells was explored in a small number of samples (91 and 85 samples). 18,22 Here, we present the results of our study by evaluating how the number of fetal cells recovered varies with maternal BMI and gestational age of the pregnancy on a larger number of samples than previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, those studies have reported variable results and it is difficult to conclude if there is a definite association between recovered fetal cell numbers and gestational age. [18][19][20][21] Furthermore, there are only two previously reported studies in which the influence of BMI on the number of fetal cells was explored in a small number of samples (91 and 85 samples). 18,22 Here, we present the results of our study by evaluating how the number of fetal cells recovered varies with maternal BMI and gestational age of the pregnancy on a larger number of samples than previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…25 Furthermore, gender identification by both FISH and PCR is reliable as early as 5 weeks of gestation. 25,26 In the present case study, we isolated 1400 intact trophoblast cells at 7 weeks of gestation that were homogeneous based on b-hCG labeling. All of the isolated cells exhibited an XY genotype to correctly identify male gender.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of over 200 specimens collected between weeks 5 and 20 of pregnancy has shown TRIC to reliably provide 500 to 1000 trophoblast cells at purities above 95%, without interference by maternal obesity. 26 It is hypothesized that TRIC could accurately identify a male fetus in pregnancies at risk of CAH prior to the time when steroid therapy would be initiated. To support the hypothesis, a clinical case is presented in which prenatal gender testing by TRIC was used in the seventh week of gestation to correctly identify male fetal cells from a pregnancy conceived by parents who previously had a child with CAH and who both harbored mutations in 21-OHD.…”
mentioning
confidence: 99%
“…and S.D.) experience ( Fritz et al , 2015b ). Whether trophoblast cells not expressing HLA-G remain longer in the cervix is unclear.…”
Section: Routes For Trophoblast Migration Into the Reproductive Tractmentioning
confidence: 99%
“…Retrieval of trophoblast cells from the endometrial canal using a cytobrush can be considered minimally invasive. The office procedure is essentially a Pap smear, and can be performed successfully between 5 and 20 weeks GA ( Fritz et al , 2015b ). Pap smears are recommended during pregnancy, and several studies that surveyed approximately 1900 pregnant women found the cytobrush procedure to be safe and associated with no serious adverse outcomes ( Orr et al , 1992 ; Rivlin et al , 1993 ; Paraiso et al , 1994 ; Holt et al , 2005 ).…”
Section: Trophoblast Retrieval and Isolation From The Cervixmentioning
confidence: 99%